New Neotropical species of Hygronemobius Hebard, 1913 (Orthoptera: Grylloidea: Nemobiinae), including a brief discussion of male genitalia morphology and preliminary biogeographic considerations of the genus - Pereira, Marcelo Ribeiro; Miyoshi, Akio Ronaldo; Martins, Luciano De Pinho; Fernandes, Maria Luiza; Sperber, Carlos Frankl; Mesa, Alejo (Zootaxa, 2013)
Three new Neotropical species of Hygronemobius Hebard are described from Atlantic Forest remnants in southeastern Brazil: Hygronemobius indaia sp. n. and Hygronemobius iperoigae sp. n. from the state of São Paulo and Hygronemobius guriri sp. n. from the state of Espírito Santo. We provide photographs of types and male genitalia, and discuss the mor-phology of male genitalia, taxonomy, calling songs and biogeographic distribution of the genus.